2016
DOI: 10.3389/fneur.2016.00195
|View full text |Cite
|
Sign up to set email alerts
|

Immununochemical Markers of the Amyloid Cascade in the Hippocampus in Motor Neuron Diseases

Abstract: BackgroundSeveral findings suggest that the amyloid precursor protein (APP) and the amyloid cascade may play a role in motor neuron disease (MND).ObjectiveConsidering that dementia is one of the most frequent non-motor symptoms in amyotrophic lateral sclerosis (ALS) and that hippocampus is one of the brain areas with greater presence of amyloid-related changes in neurodegenerative diseases, our aim was to analyze the molecular markers of the amyloid cascade of APP in pathology studies of the hippocampus of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 73 publications
4
23
1
Order By: Relevance
“…It is known that a small percentage of ALS patients have ADD pathology [7] and it was shown recently that both amyloid precursor protein (APP) and intracellular Aβ are overexpressed in the hippocampus in ALS compared to CTRL [14]. In animal models of ADD it has been shown that increasing the soluble APP fragment cleaved by α-secretase may improve cognition and rescue long-term potentiation (LTP) [34, 38].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that a small percentage of ALS patients have ADD pathology [7] and it was shown recently that both amyloid precursor protein (APP) and intracellular Aβ are overexpressed in the hippocampus in ALS compared to CTRL [14]. In animal models of ADD it has been shown that increasing the soluble APP fragment cleaved by α-secretase may improve cognition and rescue long-term potentiation (LTP) [34, 38].…”
Section: Discussionmentioning
confidence: 99%
“…In their study (1), the group measured key biomarkers of the amyloid cascade [amyloid precursor protein (APP), transactive response DNA-binding protein 43 (TDP-43), phosphorylated TDP-43 (pho-TDP43), amyloid-beta peptide (Aβ), and amyloid precursor protein-binding protein family B (Fe 65)] immunohistochemically in postmortem samples of the hippocampus of amyotrophic lateral sclerosis (ALS) and ALS–frontotemporal dementia patients. Compared to controls, they report increased levels of APP and Aβ peptide in MND patients; the latter change also correlating with cytoplasmic pho-TDP-43 expression.…”
mentioning
confidence: 94%
“…A recent article (1) encourages us to focus on some of the similarities of these diseases by demonstrating that features characteristically associated with AD are also commonly found in MND.…”
mentioning
confidence: 99%
See 2 more Smart Citations